Analisis Penerapan Variable Costing Sebagai Alat Bantu Pengambilan Keputusan Manajerial pada UMKM Keripik Pisang Sulastri Lampung - Karim, Aura Azzahra; Nur Fitri, Azahra; Winanda, Elsa Ayu; Virginia, Hanny; Niswah, Umarotun (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the application of the variable costing method as a managerial decision-making tool in the Sulastri Banana Chips MSME in Lampung, calculating the variable Cost of Goods Sold (COGS), and determining the contribution margin and break-even point (BEP). This study employed a qualitative-descriptive case study with a cost analysis approach. Data were obtained through direct interviews with the business owner and field observations. The analysis was conducted by comparing the traditional (full costing) and variable costing methods using production data for November 2025. The results showed that the COGS per package using the variable costing method was Rp6,253.75, Rp37.50 lower than the traditional method of Rp6,291.25. The contribution margin per package was Rp7,746.25 with a selling price of Rp14,000. The application of variable costing has been proven to provide more relevant and transparent cost information for short-term managerial decision-making in MSMEs, including determining minimum selling prices and evaluating special orders.